Promoting Success: Self-Accommodating Techniques for Collegiate Student Athletes - Lock, Robin H.; Layton, Carol A. (My University, 2000)
Making the transition from high school to the university setting is often difficult for many incoming freshmen including collegiate student athletes. Failure in initial classes may appear to be the result of inadequate mastery of the content presented in the course; however, additional factors may be involved. Many students both with disabilities as well as without documented learning disabilities may fail to master the content of college courses due to a lack of knowledge of their own learning needs or intrinsic processing behaviors. Student athletes both with and without documented disabilities were asked to voluntarily complete a self-report on their intrinsic processing skills as identified by the LDDI. Two students' profiles were chosen representing both learning disabled and non-disabled populations. The profiles were randomly selected. This article examined two student athletes and outlined a process that was used to facilitate the development of knowledge about personal intrinsic processing needs. Self-report information was analyzed and self-accommodating techniques were developed for the student to improve their performance in the university classroom. As a final step, ADA accommodations for the collegiate setting were also developed using the self-report information about intrinsic processing needs delineated by the student with learning disabilities.
Keywords: at-risk; skills